2016
DOI: 10.1136/vr.103812
|View full text |Cite
|
Sign up to set email alerts
|

Career aspiration in UK veterinary students: the influences of gender, self‐esteem and year of study

Abstract: (2016) 'Career aspiration in UK veterinary students: the influences of gender, self-esteem and year of study ', Veterinary Record, 179(16) , AbstractIt is widely reported that the veterinary profession is becoming increasingly female-dominated, but there are concerns that this is not represented in positions of leadership. Although there are well-documented data describing the under-representation of women in various senior veterinary positions (academic deans, practice owners, positions on professional coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
2
18
0
4
Order By: Relevance
“…The results of this study are in line with a number of empirical results that consistently report a positive relationship between selfesteem and leadership [26], between self-esteem and leadership aspirations [11], and research results between psychological variables (self-esteem, self-concept, and internal illusory control) with educational aspirations and job aspirations [14]. Castro & Armitage-Chan [27] found that students with higher confidence and self-esteem were more likely to aspire to realize their plans, then students with higher self-esteem had more positive views about learning, skills development, and educational experience, and experience less stress, all of which can positively influence the pursuit of leadership roles and aspirations for individual education going forward, both of which are dimensions of career aspirations.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study are in line with a number of empirical results that consistently report a positive relationship between selfesteem and leadership [26], between self-esteem and leadership aspirations [11], and research results between psychological variables (self-esteem, self-concept, and internal illusory control) with educational aspirations and job aspirations [14]. Castro & Armitage-Chan [27] found that students with higher confidence and self-esteem were more likely to aspire to realize their plans, then students with higher self-esteem had more positive views about learning, skills development, and educational experience, and experience less stress, all of which can positively influence the pursuit of leadership roles and aspirations for individual education going forward, both of which are dimensions of career aspirations.…”
Section: Discussionsupporting
confidence: 89%
“…The under-representation of women in practice ownership and increasingly low incomes of female employees could potentially stagnate the income of the entire profession [43,46,56,57,68]. Although, one study found that 73% of UK female veterinary students aspired to own a practice after graduating [69], indicating that women do wish to take on senior roles in a veterinary business; however may not get the opportunity. Therefore there is a significant wage gap between male and female veterinary surgeons but this also extends to starting wages.…”
Section: Women In Veterinary Medicine Anatomy and Physiologymentioning
confidence: 99%
“…3,4 An increase in non-veterinarians working in veterinary practices has occurred alongside other forces threatening to drive down veterinary salaries (including feminization of the profession). 5 Some researchers in the USA have also proposed that increasing graduate numbers, resulting in increased competition for graduate employment, may decrease salaries to such an extent that salary income fails to outweigh students' financial investment in their education. 6 These changes to the profession demonstrate the importance for veterinary students to engage with business education, in order to enhance their employability and justify a reasonable income.…”
Section: Introductionmentioning
confidence: 99%